The Djinn waits a hundred years - Khan, Shubnum (Viking, 2024)
"Rebecca meets Fatima Farheen Mirza in this sweeping, gorgeously atmospheric novel about a ruined mansion by the sea, and a young girl who unearths the true story of the tragedy that happened there a hundred years ago. Akbar Manzil was once a grand estate off the coast of South Africa. Now, nearly a century since it was built, it stands in ruins-a boardinghouse for misfits, where people come to forget or be forgotten. Seeking a new home after a painful tragedy, Sana and her effusive father are Akbar Manzil's newest residents. There they find a community of eccentrics, each suffering their own losses and likewise searching for something-escape, solace, absolution. As Sana becomes increasingly entwined in their stories, she finds herself irresistibly drawn to the history of the mansion itself: to the overgrown garden and its strange assortment of bones; to the eerie and forgotten East Wing, home to a clutter of broken and abandoned objects; and to a dusty old bedroom, unopened for decades, where she finds faded photographs of Akbar Manzil's first residents and a worn diary with entries she cannot translate. As she explores the mansion's whispering corners, she dredges up its longest resident: a djinn, the only remnant of Akbar Manzil's dark past. With its help, she discovers the story of a young woman named Meena from a hundred years prior, the original owner's second wife, who lived in the East Wing at the height of Akbar Manzil's glory, whose tragic fate is the house's ultimate secret-and whose story is the answer that Sana had been searching for all along. Sublime, heart-wrenching, and lyrically stunning-with a cast of characters that will have you crying from both laughter and sorrow-Paper Flowers is a haunting, a love story, and a mystery, all twined beautifully into one young girl's search for belonging"--